Computational Complexity - Tenreiro Machado, J.; Lopes, António (Entropy (Basel, Switzerland), 2017)
Complex systems (CS) involve many elements that interact at different scales in time and space. The challenges in modeling CS led to the development of novel computational tools with applications in a wide range of scientific areas. The computational problems posed by CS exhibit intrinsic difficulties that are a major concern in Computational Complexity Theory. [...]